Vienan naisia tutkimassa – rajan ja perinteen jäljillä - Hyry, Katja (Elore, 2005)
The article is based on the fieldwork made in Kemi (Finland) and Kiestinki (Dvina Karelia) in 1989. The topic of the research is the biographic tradition of the Karelian refugees. The article opens the experiences of the fieldwork, the experiences of two generations in the fieldwork together, and the ethical dilemmas which arose during the fieldwork. One topic of the article is the problem related to the cult of the rune singers which had a strong effect on the informants as well as on the fieldwork. The article is based on the fieldwork made in Kemi (Finland) and Kiestinki (Dvina Karelia) in 1989. The topic of the research is the biographic tradition of the Karelian refugees. The article opens the experiences of the fieldwork, the experiences of two generations in the fieldwork together, and the ethical dilemmas which arose during the fieldwork. One topic of the article is the problem related to the cult of the rune singers which had a strong effect on the informants as well as on the fieldwork.